Fabrication of Cu: ZnO thin film sensor for ethanol vapor detection - Robin Simkhada; Dalton R. Gibbs; Soma Dhakal; Dipak Oli; Rishi Ram Ghimire; Deependra Das Mulmi; Leela Pradhan Joshi (Bibechana)
For a long time, metal oxide semiconductor (MOS) based gas sensors have been widely used in domestic, commercial, and industrial sectors to detect harmful gases. The performance of such sensors is significantly enhanced by appropriate doping of suitable materials into MOS such as ZnO and SnO2. This work showcases the design, analysis, and use of a Cu-doped ZnO (Cu: ZnO) film tailored for detecting traces of ethanol vapor at lower temperatures. Herein, various Cu: ZnO films have been fabricated on glass substrates using a spin coater followed by annealing at 600  for 1 hour in a muffle furnace. So-prepared samples have been characterized using X-ray diffraction, Energy Dispersive Analysis X-ray (EDAX), UV-visible spectrophotometer, and Scanning Electron Microscopy (SEM). The XRD analysis showed a polycrystalline nature with preferred orientation along (100) and (002) crystal planes. The morphology study showed their porous and granular surface structure. These films' elemental analysis demonstrated the good incorporation of Cu into the ZnO matrix. The UV-visible results showed a significant decrease in the band gap from 3.28 eV for undoped ZnO to 3.20 eV for Cu: ZnO films. Ultimately, as-prepared Cu: ZnO thin films were used for sensing ethanol vapor at temperatures ranging from 100 to 300 . The result showed a maximum sensitivity of 70.60  at a reduced temperature of 140  at 4% Cu: ZnO thin, which implies that Cu: ZnO is suitable for developing the gas sensors for upcoming future generations.